The Truman Court : Law and the Limits of Loyalty - James, Rawn (Book collections on Project MUSE., 2021)
"The Truman Court: Law and the Limits of Loyalty argues that the years between FDR's death in 1945 and Chief Justice Earl Warren's confirmation in 1953-the dawn of the Cold War-were, contrary to widespread belief, important years in Supreme Court history. Never before or since has a president so quickly and completely changed the ideological and temperamental composition of the Court. With remarkable swiftness and certainty, Truman constructed a Court on which he relied to lend constitutional credence to his political agenda"--